2020
DOI: 10.1111/anec.12763
|View full text |Cite
|
Sign up to set email alerts
|

How are ECG parameters related to cardiac magnetic resonance images? Electrocardiographic predictors of left ventricular hypertrophy and myocardial fibrosis in hypertrophic cardiomyopathy

Abstract: Background Structural myocardial changes in hypertrophic cardiomyopathy (HCM) are associated with different abnormalities on electrocardiographs (ECGs). The diagnostic value of the ECG voltage criteria used to screen for left ventricular hypertrophy (LVH) may depend on the presence and degree of myocardial fibrosis. Fibrosis can cause other changes in ECG parameters, such as pathological Q waves, fragmented QRS (fQRS), or repolarization abnormalities. Methods We investigated 146 patients with HCM and 35 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Previous studies have reported that, in patients with hypertrophic cardiomyopathy, low QRS voltage is associated with cardiac fibrosis as assessed by magnetic resonance imaging. 11,12 Taken together, a high LVMI-to-QRS-voltage ratio is not simply a marker of identifying cardiac amyloidosis, but comprehensive marker of myocardial structural changes due to myocardial fibrosis and infiltration into the myocardium, which is helpful for risk stratification and understanding pathophysiology in heterogeneous patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that, in patients with hypertrophic cardiomyopathy, low QRS voltage is associated with cardiac fibrosis as assessed by magnetic resonance imaging. 11,12 Taken together, a high LVMI-to-QRS-voltage ratio is not simply a marker of identifying cardiac amyloidosis, but comprehensive marker of myocardial structural changes due to myocardial fibrosis and infiltration into the myocardium, which is helpful for risk stratification and understanding pathophysiology in heterogeneous patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Of 535 patients enrolled in the JASPER registry, the following patients were excluded: patients who died during their hospitalization (n = 7); patients without body surface area data, or echocardiogram during hospitalization (n = 16); patients without electrocardiogram (ECG) assessment during hospitalization (n = 206); and patients whose QRS voltage on ECG showed abnormal values (SV1 + RV5 ≥ 10 mV) that were not physiologically possible and assumed to be input errors (n = 16) considering previously reported studies. 11,12 A total of 290 patients were included in this analysis.…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…With cardiac magnetic resonance imaging, fQRS has been shown to be associated with scar tissue in many cardiac diseases [27][28][29][30]. In patients with acromegaly, chronic excess of GH and IGF-1 secretion causes biventricular concentric hypertrophy and then interstitial fibrosis develops, which is accompanied by increased extracellular collagen deposition, lympho-mononuclear infiltrations, and myofibrillar derangement [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agents can trigger apoptosis or cause necrotic myocyte death. fQRS occurs when ventricular depolarization (VD) becomes abnormal and has been identified as an ECG biomarker of myocardial fibrosis and can be used to predict adverse cardiovascular events [ 12 , 20 ].…”
Section: Discussionmentioning
confidence: 99%